1976
DOI: 10.2151/jmsj1965.54.6_361
|View full text |Cite
|
Sign up to set email alerts
|

Wind Profile and Kinetic Energy Budget in the Mixed Laye of Polar Air-Mass Transformed over Kuroshio Region

Abstract: The characteristic features of the wind profile, the momentum and kinetic energy budget in the mixed layer of the polar air-mass transformed over the Kuroshio region are analyzed for the three periods of polar outbreak in AMTEX '74 and '75.While there is a strong geostrophic wind shear in the mixed layer, the wind distribution in the mixed layer is characterized by the almost vertically uniform northerly winds. In the lower part of the mixed layer, the strong ageostrophic winds are directed toward the low pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 26 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Therefore the winter monsoon season is the dry season, in general, over East Asia. An airmass transformation takes place, when the cold dry continental airmass flows over the warm sea surface (Ninomiya, 1968(Ninomiya, , 1976Ninomiya and Akiyama, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the winter monsoon season is the dry season, in general, over East Asia. An airmass transformation takes place, when the cold dry continental airmass flows over the warm sea surface (Ninomiya, 1968(Ninomiya, , 1976Ninomiya and Akiyama, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…In the AMTEX region during the cold air outbreaks, Ninomiya (1976) performed a momentum budget analysis and showed that the excess of the pressure gradient force over the Coriolis force, i.e., -* (u -ug) , and the frictional force are the major terms in the momentum balance in the northerly wind component, which is almost parallel to the lower wind direction. Furthermore, the budget analysis indicates that the pressure gradient force in the downstream direction decreases with height.…”
Section: Feedback Effect Of the Large-scale Motion On Mixed Layer Devmentioning
confidence: 99%
“…The first one is the difference of the role of the horizontal advection ; it has a decelerating effect in the numerical experiment, while it has an accelerating effect in the observational analysis (Ninomiya, 1976 andNitta andSo, 1980). The acceleration rate due to the pressure gradient force caused by the heat supply from the sea can be estimated as (gF*(0)(1+k)(2*um)-1), while the deceleration rate due to the surface friction is estimated as (CDu2m/h).…”
Section: Feedback Effect Of the Large-scale Motion On Mixed Layer Devmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninomiya (1976) studied the kinetic energy budget in the mixed layer over the Kuroshio. Kung (1977b) analyzed the large-scale energy transformation over the Kuroshio region.…”
mentioning
confidence: 99%